The role of atmospheric non-thermal plasma in the bacteria inactivation - Khalaf, Thamir H. (Iraqi Journal of Physics, 2019)
Non-thermal atmospheric pressure plasma has emerged as a new promising tool in medicine and biology. In this work, A DBD system was built as a source of atmospheric pressure non-thermal Plasma suitable for clinical and biological applications. E. coli and staphylococcus spp bacteria were exposed to the DBD plasma for a period of time as inactivation (sterilization) process. A series of experiments were achieved under different operating conditions. The results showed that the inactivation, of the two kinds of bacteria, was affected (increasing or decreasing) according to operation conditions because they affects, as expected, the produced plasma properties according to those conditions.